Effect of garlic plus onion extract on productive performance and intestinal morphometry in broiler chickens - Pujada A., Hilario (2025)
The effect of garlic and onion extract supplementation on the productive performance and intestinal morphometry of broiler chickens was evaluated. A total of 150 male chickens of the Cobb 500 line were randomly distributed in three treatments: Basal control diet (T0), Basal diet plus 0.05% Zinc bacitracin -AGP- at 10% (T1) and basal diet plus 1.5% mixture in equal proportion of garlic and onion extract (T2). At 42 days of age, five chickens were slaughtered per treatment to determine carcass yield, abdominal fat accumulation and to collect samples of the duodenum, jejunum and ileum for morphometric examination. Both T1 and T2 achieved better body weight, daily weight gain, feed conversion, carcass yield and a lower abdominal fat deposit (p<0.05) compared to T0. Feed intake was similar in all treatments (p>0.05). T2 and T1 presented better intestinal morphometry compared to T0. In the duodenum they had a higher (p<0.05) villus height, while the width was greater in the jejunum and ileum (p<0.05), a lower crypt depth was recorded in the duodenum and ileum (p<0.05) and a higher A/P ratio in the duodenum (p<0.05). It is concluded that supplementation with garlic and onion extract produces comparable results to those obtained with the AGP treatment and is presented as a viable alternative for its replacement.